2014
DOI: 10.1016/j.pneurobio.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Progress in translational research on intracerebral hemorrhage: Is there an end in sight?

Abstract: Intracerebral hemorrhage (ICH) is a common and often fatal stroke subtype for which specific therapies and treatments remain elusive. To address this, many recent experimental and translational studies of ICH have been conducted, and these have led to several ongoing clinical trials. This review focuses on the progress of translational studies of ICH including those of the underlying causes and natural history of ICH, animal models of the condition, and effects of ICH on the immune and cardiac systems, among o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 257 publications
0
109
0
Order By: Relevance
“…18 We analyzed the gene expression profiles of several chemokines in the hemorrhagic brains 24 hours after ICH. The results revealed that ICH strongly elevated the levels of chemokine (C-X-C motif) ligand 1 (CXCL1), CX3CL1, and the chemokine (C-C motif) receptor 1 (CCR1) when compared with the sham-operated group ( Figure 1A).…”
Section: Recombinant Adamts 13 Attenuated Ich-associated Cerebral Infmentioning
confidence: 99%
“…18 We analyzed the gene expression profiles of several chemokines in the hemorrhagic brains 24 hours after ICH. The results revealed that ICH strongly elevated the levels of chemokine (C-X-C motif) ligand 1 (CXCL1), CX3CL1, and the chemokine (C-C motif) receptor 1 (CCR1) when compared with the sham-operated group ( Figure 1A).…”
Section: Recombinant Adamts 13 Attenuated Ich-associated Cerebral Infmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) is an intractable neurological malady with high morbidity and mortality 1. Despite stable incidence rates and declining mortality rates over the past 2 decades, motor dysfunction remains an intractable problem with no clinically available interventions except rehabilitation 2.…”
mentioning
confidence: 99%
“…These results suggest that compounds that interrupt the free radical cascade might improve ICH outcome. Although there are a number of ongoing clinical trials (Xi et al, 2014), currently there is no FDA-approved treatment for ICH and the use of alternative means such as green tea, which could be part of people's diet, could be an interesting, inexpensive and easy way to avoid some ICH sequelae without side effects. In this study, we did not show any difference on GSH levels and GPx activity.…”
Section: Discussionmentioning
confidence: 99%